2017
DOI: 10.1016/j.semcdb.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Overcome tumor heterogeneity-imposed therapeutic barriers through convergent genomic biomarker discovery: A braided cancer river model of kidney cancer

Abstract: Tumor heterogeneity, encompassing genetic, epigenetic, and microenvironmental variables, is extremely complex and presents challenges to cancer diagnosis and therapy. Genomic efforts on genetic intratumor heterogeneity (G-ITH) confirm branched evolution, support the trunk-branch cancer model, and present a seemingly insurmountable obstacle to conquering cancers. G-ITH is conspicuous in clear cell renal cell carcinoma (ccRCC), where its presence complicates identification and validation of biomarkers and thwart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 112 publications
0
50
0
Order By: Relevance
“…Among the 451 upregulated genes in ICD (+) chRCC, 401 (89%) were up in WGD (+) ccRCC compared with WGD (-) ccRCC, and among the 525 downregulated genes in ICD (+) chRCC, 415 (79%) were down (χ 2 test, P < 1 × 10 -30 ) ( Figure 6A). Hence, the molecular signature conferred by ICD in chRCC is highly concordant with that by WGD in ccRCC, implying a shared pathway convergent evolution between 2 kidney cancer subtypes (28,36).…”
Section: There Are Shared Molecular Features Between the Icd (+) Casementioning
confidence: 76%
See 2 more Smart Citations
“…Among the 451 upregulated genes in ICD (+) chRCC, 401 (89%) were up in WGD (+) ccRCC compared with WGD (-) ccRCC, and among the 525 downregulated genes in ICD (+) chRCC, 415 (79%) were down (χ 2 test, P < 1 × 10 -30 ) ( Figure 6A). Hence, the molecular signature conferred by ICD in chRCC is highly concordant with that by WGD in ccRCC, implying a shared pathway convergent evolution between 2 kidney cancer subtypes (28,36).…”
Section: There Are Shared Molecular Features Between the Icd (+) Casementioning
confidence: 76%
“…In patients 2 and 3, TP53 mutation was absent in the primary tumor but present in the metastatic lymph nodes. In patient 4, the same TP53 N310Tfs mutation was present in primary and metastatic lymph node samples, whereas 5 different PTEN mutations were detected and distributed among samples, demonstrating convergent mutation evolution of PTEN (28,31,32). In patient 5, both TP53 and PTEN mutations were detected in the dominant clone and hence present in both primary and metastatic liver samples.…”
Section: Wgs On 5 M-hrcc Cases Identifies Recurrent Genomic Aberrationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, owing to the predominance of clear cell histology in metastatic disease (83–88%) 12,13 , tumours with non-clear cell histology have been grouped as ‘nccRCC’ (Table 1) for feasibility in conducting clinical trials 1416 . Furthermore, recent cancer genomic studies have revealed an overt complexity of intra-tumour 1719 and inter-tumour 7,20 heterogeneity in ccRCC, which could contribute to the heterogeneous clinical outcomes observed 2123 .…”
Section: Introductionmentioning
confidence: 99%
“…It is now a known fact that a tumour is not a homogenous tissue and in recent years, many researchers have focused on the heterogeneity of the tumour tissue. [14][15][16][17][18] The outer layers of a tumour can proliferate easily. These cells have enough space to proliferate, and sufficient access to blood as a source of oxygen and nutrition and a readily accessible stream for getting rid of all the metabolic wastes.…”
Section: Introductionmentioning
confidence: 99%